Atomic origin of the spin-polarization of the Co2FeAl Heusler compound. (29th January 2016) - Liang, Jaw-Yeu; Lam, Tu-Ngoc; Lin, Yan-Cheng; Chang, Shu-Jui; Lin, Hong-Ji; Tseng, Yuan-Chieh
Abstract: Using synchrotron x-ray techniques, we studied the Co2 FeAl spin-polarization state that generates the half-metallicity of the compound during an A2 (low-spin)  →  B2 (high-spin) phase transition. Given the advantage of element specificity of x-ray techniques, we could fingerprint the structural and magnetic cross-reactions between Co and Fe within a complex Co2 FeAl structure deposited on a MgO (0 0 1) substrate. X-ray diffraction and extended x-ray absorption fine structure investigations determined that the Co atoms preferably populate the (1/4, 1/4, 1/4) and (3/4, 3/4, 3/4) sites during the development of the B2 phase. X-ray magnetic spectroscopy showed that although the two magnetic elements were ferromagnetically coupled, they interacted in a competing manner via a charge-transfer effect, which enhanced Co spin polarization at the expense of Fe spin polarization during the phase transition. This means that the spin-polarization of Co2 FeAl was electronically dominated by Fe in A2 whereas the charge transfer turned the dominance to Co upon B2 formation. Helicity-dependent x-ray absorption spectra also revealed that only the minority state of Co/Fe was involved in the charge-transfer effect whereas the majority state was independent of it. Despite an overall increase of Co2 FeAl magnetization, the charge-transfer effect created an undesired trade-off during the Co–Fe exchange interactions, because of the presence of twice as many X sites (Co) as Y sites (Fe) in the Heusler X 2 YZ formula. This suggests that the spin-polarization of Co2 FeAl is unfortunately regulated by compromising the enhanced X (Co) sites and the suppressed Y (Fe) sites, irrespective of the development of the previously known high-spin-polarization phase of B2 . This finding provides a possible cause for the limited half-metallicity of Co2 FeAl discovered recently. Electronic tuning between the X and Y sites is necessary to further increase the spin-polarization, and likely the half-metallicity as well, of the compound.